Yes Logo Uncovering the Recipes of Branding Success in the World's Largest Consumer Market - Wang, Jiazhuo George; Qin, Shuo.; Wang, Allison (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book focuses on how to succeed in China, the globe's largest consumer market, through the branding market strategy. What are the undisclosed recipes that brands can follow to capture the attention and emotion of consumers in China? What's the magical key to open the locked doors? The answer to these questions would be intriguing for many readers outside China, including but not limited to executives of global brands, owners of medium-and-small-sized businesses aiming for the global market, branding/marketing professionals, financial investors and analysts, business professors and researchers in universities and colleges, graduate and undergraduate students, and readers with an interest on these topics in the general public. In comparison with many case studies that focus on only a single or few cases, or else lean toward being a macro-discussions of China's consumer market without in-depth analysis of representative cases, this book provides both. Many branding strategies, programs, and activities presented in this book are of the innovative type, which could be very fresh and interesting to readers. Many of the in-depth analyses and specific insights presented in this book are provided by well-recognized business analysts/writers, which may not be available in other publications. Overall, this book provides readers with the opportunity to receive some valuable new knowledge about how to succeed in the globe's largest consumer market, providing foodstuff for both thought and enjoyment.
.1. Xiaomi: An Internet-Driven Miracle -- Nongfu Spring: Down to the Soul of a Brand -- Haier: A Brand That Started with A Smashed Fridge -- Anta Sports: Rising with the Recreation of Global Brands -- BYD: A Disrupter of the Emerging Market -- WeChat: A Way of Life in the Information Age -- DingTalk: The Digital Way of Working in China -- The Ocean Engine: A Front Runner in Digital Marketing -- A Lifestyle in the Third Place: Starbucks' China Journey -- Creating Beauty that Moves the World: L'Oréal in China.
Keywords: Branding (Marketing).; Telemarketing; Internet marketing; Consumer behavior; Branding; Digital Marketing; Consumer Behavior